Financial Reform : What Shakes It? What Shapes It? - Mody, Ashoka (Economic Issues; Economic Issues ;, 2007)
Financial sector liberalization was high on the agenda of policymakers during the last quarter of the twentieth century. But there were significant differences in the pace and scale of reform. This pamphlet examines the factors triggering-or impeding and even reversing-financial reform in 35 economies, both industrial and developing.